Experimental study on circular steel tube-confined reinforced UHPC columns under axial loading. (1st March 2021) - Wei, Jiangang; Xie, Zhitao; Zhang, Wei; Luo, Xia; Yang, Yan; Chen, Baochun
Highlights: Five types of stub columns are tested under compressive axial loading. Effects of the steel fibers on the behavior of UHPC are investigated. Predictions of the ultimate bearing capacities of the steel tube-confined reinforced UHPC (STCRU) columns are implemented. Abstract: This paper investigates the compressive behavior of circular steel tube-confined reinforced ultrahigh-performance concrete (UHPC) columns. An experiment was conducted consisting of axial loading applied to 18 stub columns ( λ  = 4 L/D  = 13), including steel tube-confined reinforced UHPC (STCRU) columns, steel tube-confined UHPC (STCU) columns, UHPC-filled steel tube (UFST) columns, steel tube-confined reinforced concrete (STCRC) columns, and reinforced UHPC (RU) columns. The compressive behavior was also investigated by varying the addition of steel fibers. The failure mode of all the columns was shear failure except for the explosive failure of the RU columns without steel fibers and the drum-type failure of the STCRC columns. Interestingly, the addition of steel fibers greatly improved the strength and ductility of the RU columns. Finally, a reasonable formula for predicting the bearing capacity of STCRU columns was provided to overcome the application limits of existing specifications, and the formula can describe the axial bearing capacity of stub STCRU columns better than other approaches.